Growth of pure ground-glass lung nodule detected at computed tomography - Aoki, Takatoshi (J Thorac Dis, 2015)
The natural history of pure ground-glass nodules (GGNs) of the lung has been gradually revealed. Approximately 10-25% of pure GGNs increases in size or grow the solid component, while others remain unchanged for years. Further investigations including the relationship between the successive change on computed tomography (CT) and the molecular change may be necessary to determine the appropriate management strategy of pure GGNs.